Analysis of the health of Indonesian conventional and sharia BUMN Banks for the period 2020-2022 - Ganang Ikhwanudin; Zulfa Irawati (Jurnal Mantik, 2024)
This research aims to determine the health condition of conventional and Sharia state-owned banks between 2020 and 2022. This research uses the RGEC technique approach combined with quantitative descriptive methods. The RGEC method includes four factors: risk profile, good corporate governance, income, and capital. Data is taken from the annual report released by the company. The research results show that: 1) The NPL ratio of conventional and Sharia state-owned banks has a very healthy rating. 2) LDR and FDR ratios, conventional and Sharia state-owned banks have the title of healthy and relatively healthy. 3) The Good Corporate Governance ratio of conventional and Sharia state-owned banks is healthy. 4) The ROA ratio of conventional and Sharia state-owned banks is very healthy and relatively healthy. 5) The NIM ratio of conventional and Sharia state-owned banks has the title of being very sound and healthy. 6) The CAR ratio of Conventional and Sharia BUMN Banks has a very healthy title. Overall, the RGEC method assessment of the health level of conventional and Sharia state-owned banks from 2020 to 2022 shows that conventional banks have better performance and received the Very Healthy predicate than Islamic banks, which received the Healthy predicate